The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.3892/or.2015.4081
|View full text |Cite
|
Sign up to set email alerts
|

Astrocyte elevated gene-1 regulates CCL3/CCR5-induced epithelial-to-mesenchymal transition via Erk1/2 and Akt signaling in cardiac myxoma

Abstract: In recent years, astrocyte elevated gene-1 (AEG-1) has been reported as a key mediator that is involved in the epithelial-to-mesenchymal transition (EMT) process. However, the mechanisms underlying CCL3/CCR5-AEG-1 pathway-mediated EMT in cardiac myxoma (CM) has not been well featured till now. We used immnohistochemistry and immunoblotting to assess the expression of CCR5 and AEG-1 in 30 cases of CM tissues and cells. Subsequently, cultured CM cells were treated with si-AEG-1 or si-CCR5 and then subjected to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 28 publications
(29 reference statements)
1
10
0
Order By: Relevance
“…Additionally, AEG-1 performs its functions through mitogen-activated protein kinase, extracellular signal-regulated kinase, phosphatidylinositol 3-kinase/protein kinase B, and signal transducer and activator of transcription 3 signalling pathways. [40][41][42][43] These findings suggest that these signalling pathways may be also involved in the functions of AEG-1 in melanoma. In the present study, AEG-1 silencing was found to inhibit the growth of melanoma cells in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Additionally, AEG-1 performs its functions through mitogen-activated protein kinase, extracellular signal-regulated kinase, phosphatidylinositol 3-kinase/protein kinase B, and signal transducer and activator of transcription 3 signalling pathways. [40][41][42][43] These findings suggest that these signalling pathways may be also involved in the functions of AEG-1 in melanoma. In the present study, AEG-1 silencing was found to inhibit the growth of melanoma cells in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 82%
“…Consistently, in our study, the activation of the Wnt/β‐catenin signalling pathway was inhibited by AEG‐1 silencing, which indicates that AEG‐1 may exert its oncogenic role in melanoma cells through the Wnt/β‐catenin signalling pathway. Additionally, AEG‐1 performs its functions through mitogen‐activated protein kinase, extracellular signal‐regulated kinase, phosphatidylinositol 3‐kinase/protein kinase B, and signal transducer and activator of transcription 3 signalling pathways . These findings suggest that these signalling pathways may be also involved in the functions of AEG‐1 in melanoma.…”
Section: Discussionmentioning
confidence: 91%
“…AEG-1 has been proven to exert functions in the development of various types of cancer, including liver cancer ( 19 , 29 ), breast cancer ( 30 ), colorectal cancer ( 18 , 31 ), lung cancer ( 32 ) and ovarian cancer ( 33 ). It has been reported that C-C motif chemokine 3/C-C chemokine receptor type 5-induced EMT may be regulated by AEG-1 via extracellular signal-regulated kinase 1/2 and RAC-α serine/threonine protein kinase signaling in cardiac myxoma ( 34 ). In addition, a study analyzed the role of miR-302c-3p in suppressing the invasion and proliferation of glioma cells by downregulating AEG-1 expression ( 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, many studies have established a positive correlation between AEG-1 expression and EMT status in cancer progression, including in lung cancer 29 , cardiac myxoma 30 , glioblastoma 31 and tongue squamous cell carcinoma (TSCC) 32 . In our study, we found increased expression of vimentin and decreased expression of E-cadherin in OSCC cell lines stably overexpressing AEG-1, which suggests that AEG-1 promotes EMT.…”
Section: Discussionmentioning
confidence: 99%